Efektivitas Model Flipped Classroom Berbasis Problem Based Learning dalam Meningkatkan Kemampuan Berpikir Kritis Mahasiswa - Sarah Inayah; Ari Septian; Elsa Komala (Universitas Sarjanawiyata Tamansiswa, 2021)
The purpose of this study is to test the effectiveness of the Flipped Classroom Model Based on Problem Based Learning to improve students' critical thinking skills whose learning device have been developed. The learning device are implemented in the mathematics education study program in the Faculty of Teacher Training and Education, Suryakancana University. Critical thinking is one of the 21st century skills. To improve critical thinking skills, it can be done by choosing the right learning model. The learning model is Problem Based Learning (PBL). The flipped classroom model is also suitable for developing the skills needed to face the industrial revolution or better known as the 21st century skills. This research was conducted specifically for the Data Processing course in the Mathematics Education study program, FKIP Suryakancana University. The research carried out refers to the Research and Development (R&D design) design from Borg and Gall. The results of the implementation show that the Flipped Classroom Model Based on Problem Based Learning is effective in improving critical thinking skills.